Methods and approaches in teaching languages in the context of updated content of education - Khajayeva, Zh.B.; Stambekova, A.S.; Drink, B. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
The article is devoted to the method and approaches in teaching languages in the context of the updated content of education. The existing normative documents in the educational system of the Republic of Kazakhstan are considered. Adoption of these documents contributed to changes in the political, economic and social spheres of the country, renewal of the content of education and new directions. The article reveals the content of the concept, as a «method», «approach», «teaching languages». The article analyzes the views of domestic and foreign researchers on the definition, significance of methods and approaches in teaching languages, which showed that success in teaching languages, without a doubt, largely depends on what methods and approaches are used to achieve it. This direction is also complemented by consideration of the newest methods and approaches in the contextof the updated content of education. Namely, a new wave of the education system in Kazakhstan is aimed at modernizing the national system of multilevel education, improving the quality of personnel training, taking into account the needs of the individual and society. Therefore, one of the criteria of the modern Kazakhstani education system is the language competence (Kazakh, Russian and English). What made it possible to conclude that to become successful in the modern information society, children and young people should participate in more effective forms of active, collaborative, integrated and interactive learning, providing new skills and abilities for use in life situations and further personal development.
Білім берудің жаңартылған мазмұны контексінде тілдерді оқыту əдістері мен тəсілдері
Методы и подходы в обучении языкам в контексте обновленного содержания образования
Keywords: updated content of education; education system; language teaching; methods and approaches; educational programs; foreign language